2016
DOI: 10.1016/j.conctc.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

A randomized placebo-controlled trial of the effect of coffee consumption on insulin sensitivity: Design and baseline characteristics of the Coffee for METabolic Health (COMETH) study

Abstract: BackgroundCoffee consumption has been consistently associated with a lower risk of type 2 diabetes mellitus in cohort studies. In addition, coffee components increased insulin sensitivity in animal models. However, data from intervention studies on the effect of coffee consumption on glucose metabolism have been limited by small sample sizes, lack of blinding, short follow-up duration and the use of surrogate indices of insulin sensitivity. We designed the Coffee for Metabolic Health (COMETH) study to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Coffee consumption and coffee micronutrient components have been suggested to improve glucose metabolism, lower inflammation, and decrease liver damage in animal models [ 12 , 13 ]. Further evidence suggests that it improves endothelial function, aids in loss of fat mass and is associated with favorable plasma biomarkers of metabolic and inflammatory pathways [ 14 , 15 , 16 ]. A recent metanalysis of randomized controlled trials by Ramli et al investigated the effects of coffee consumption on anthropometric measurements, glycemic indices, lipid profiles, and blood pressure and found all of these parameters were improved by green coffee extract supplementation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coffee consumption and coffee micronutrient components have been suggested to improve glucose metabolism, lower inflammation, and decrease liver damage in animal models [ 12 , 13 ]. Further evidence suggests that it improves endothelial function, aids in loss of fat mass and is associated with favorable plasma biomarkers of metabolic and inflammatory pathways [ 14 , 15 , 16 ]. A recent metanalysis of randomized controlled trials by Ramli et al investigated the effects of coffee consumption on anthropometric measurements, glycemic indices, lipid profiles, and blood pressure and found all of these parameters were improved by green coffee extract supplementation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes (T2D) is a leading cause of mortality and morbidity worldwide [ 1 2 3 4 ], with an estimated prevalence of 9.3% [ 1 ], 67.9 million disability-adjusted life-years [ 2 ] and increase in treatment cost [ 3 ] worldwide. Evidence for the physiological significance of habitual coffee consumption on T2D manifestations keeps evolving, with some cohort studies [ 5 6 7 8 ] and randomized trials [ 9 10 ] suggesting an inverse association, but others [ 11 12 ] found a null association. The limitations of these trials included small sample sizes and a short follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…Coffee is among the most extensively consumed drinks globally; it contains many effective anti-diabetic compounds, including caffeine, kahweol, cafestol, and chlorogenic acid [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. On the other hand, literature reported that high coffee consumption is associated with some adverse effects such as gastrointestinal disturbances, tachycardia, and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%